Level of development as a determinant of innovation capability. Evidence for 132 economies using artificial neural networks - Morales Sánchez, Mario Alberto; Díaz Rodríguez, Héctor Eduardo (Estudios de Economía, 2025)
Innovation is increasingly recognized as a determinant of the level of economic activity; however, studies that analyze the determinants of innovation do not usually pay attention to the levels of development of the economies in which these processes occur. This paper aims to analyze whether the impact of the factors that determine innovation is the same for economies with different levels of development, or if, on the contrary, there is a differentiated hierarchical order of these factors. To do this, data from 132 countries in the period 2013-2021 are analyzed using artificial neural networks. The results show that the determinants of innovation have a different impact depending on the level of development of the economies. A detailed analysis of the order of impact of the variables that affect innovation allows us to conclude that it is necessary to consider the hierarchical order of the variables to understand how the different innovation processes occur and how they impact the determination of the product per inhabitant, otherwise; public policies aimed at encouraging innovation can be sterile.